SOCIOEMOTIONAL EFFECT AND MORAL DEVELOPMENT ON LEARNING OUTCOMES OF INFORMATICS MANAGEMENT STUDENTS AMIK LAMAPPAPOLEONRO SOPPENG - Nurhadiah, Nurhadiah; Fadli, Zul; Suwandi, Ihsanulfu'ad (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This study aims to describe and influence sosioemosi and moral development of the students' learning achievement in information management Amik Lamappapoleonro. The study was ex-post facto nature of causality. Subjects in this study were students information management Amik Lamappapoleonro year 2019/2020 were taken using the Proportional stratified random sampling. Data were analyzed with descriptive statistics and path analysis (path anlysis). Research results show that: (1) Most of the students of information management in Amik Lamappapoleonro have: self-concept and category of being, self-esteem with the high category, with the category of high moral, cognitive learning achievement with low category, and affective with high category, (2) Moral students information management category is very high, (3) The cognitive learning achievement of information management students are in the medium category.